FcγRIIIA -activating antibodies in dengue virus infection reveals a distinct transient cross-reactive profile - Soto-Garita, Claudio; Murillo, Tatiana; Hengel, Hartmut; Corrales-Aguilar, Eugenia (Frontiers in Immunology, 2025)
Dengue viruses belong to the genus Flavivirus and consist of a serocomplex of four serotypes (DENV-1, DENV-2, DENV-3, and DENV-4). As arthropod-borne viruses (arboviruses), their transmission is mediated primarily by the vector Aedes aegypti. Antiviral immune response is one of the most crucial factors influencing the progression from uncomplicated to severe dengue virus (DENV) infection. Two types of antibody responses are elicited during a DENV infection: one specific to the infecting serotype (serotype-specific or homotypic response) and another that cross-reacts with other serotypes (cross-reactive or heterotypic response). Both responses play roles in the protection against and in the induction of immunopathogenesis of DENV disease. In the case of the humoral immune response, the balance between protective and pathogenic effects mediated by antibodies (antibody-dependent enhancement, ADE) is highly dynamic and influenced by multiple factors. Although many downstream effector mechanisms depend on antibody recognition by Fc-gamma receptors (FcγRs) present on immune effector cells, this interaction is traditionally not considered when evaluating antibody properties. Specifically, FcγRIIIA has been implicated in both protection and immunopathogenesis of virus infection. To assess its role within the humoral immune response to DENV, we took advantage of FcγRIIIA-CD3ζ reporter cells and tested receptor activation by polyclonal sera from individuals with past and acute DENV infections. In addition, the neutralizing capacity and the potential enhancement of infection were analyzed. The FcγRIIIA activation assay revealed a humoral profile distinct from neutralization and immunopotentiation, primarily mediated by cross-reactive antibodies. Notably, this profile increases during the post-acute period but disappears within two years after infection. Because these two types of antibodies are found during both the cross-protective and disease-enhancing (immunopotentiation) phases, their exact function in each situation is still not clearly understood. The results of this study provide a valuable measurement of the effector function of anti-DENV antibodies, contributing to the understanding of their role in both protective and disease enhancing courses of DENV infection.